Total Quality Management Through Lecturer Assessment With Students to Improve Graduate Quality - Sutirna Sutirna (ADI Journal on Recent Innovation, 2020)
Total Management System or abbreviated as TQM is a management system quality that is focused on the customer (Customer focused) by involving all levels of employees in making improvements or continuous improvements (in a manner continuously). Total Quality Management or TQM uses strategy, data and effective communication to integrate quality discipline into culture and company activities. In short, Total Quality Management (TQM) is a management approach to achieve long-term success through satisfaction Customer (Customer Satisfaction). Lecturers are the spearhead of a TQM in college with always carry out Tri Dharma College, but keep in mind that customer satisfaction (in this case students) is the main key to the implementation of the tri dharma of the university high, because with the assessment of students we will be able to find out weaknesses what we have done in PBM. With this weakness, the lecturer is obliged to make changes so that TQM is achieved so that our graduates' expectations will be become competitive with overseas college graduates. The results of this study concluded that the assessment of the implementation of the learning process most lecturers have done from the preparation, implementation and evaluation stages states agree that the stages are prepared in advance by the lecturer before carrying out the lecture process.